Tax reforms and environmental policies for Italy - Marco Stampini (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper focuses on the relationship between tax reforms and environmental quality in Italy. First, we analyse some of the characteristics of the tax system. Within a dynamic model, we estimate the marginal distortion introduced by different taxes and show that the system is far from being optimal, at least in terms of efficiency. We then consider some possible tax reforms, keeping into account both the effect on utility and the impact on pollution. Finally, we design a tax reform with a specific environmental goal, i.e. the reduction of polluting emissions by 10%, and show the economic effects of this policy.
Keywords: H2; D62; D58; 330; Tax reforms; environmental taxes; general equilibrium; Steuersystem; Steuerwirkung; Ökosteuer; Steuerreform; Italien